Women and development - Casal, Lourdes; Joseph, Suad; Pala, Achola; Seidman, Ann (Racine, Winconsin: Johson Foundation, 1977)
"Een workshop bijeengeroepen door : Center dor Research and Devlopment - Wellesley College, in samenwerking met : The Johnson Foundation"